2017
DOI: 10.1177/1060028017694050
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Global Strategies to Prevent Hospital-Onset Clostridium difficile Infection: Targeting Proton Pump Inhibitors and Probiotics

Abstract: A collaborative, multifaceted educational initiative directed at highlighting the risks associated with PPI use was effective in reducing PPI prescribing. The implementation of a probiotic bundle added to antibiotic order sets was effective in increasing probiotic use. These interventions were associated with a decrease in incidence of HO-CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In a study reported by Lewis et al, multifaceted strategies aimed at preventing Clostridium difficile colitis succeeded in decreasing PPI use. After one year of such a program, the overall number of PPI prescriptions decreased by 14% 20 . Taken together with that reported herein, these results suggest that achieving a sustainable reduction of the prescribed quantities of both oral and IV PPIs requires sustained interventions.…”
Section: Resultssupporting
confidence: 77%
“…In a study reported by Lewis et al, multifaceted strategies aimed at preventing Clostridium difficile colitis succeeded in decreasing PPI use. After one year of such a program, the overall number of PPI prescriptions decreased by 14% 20 . Taken together with that reported herein, these results suggest that achieving a sustainable reduction of the prescribed quantities of both oral and IV PPIs requires sustained interventions.…”
Section: Resultssupporting
confidence: 77%
“…Although decreases in HO-CDI can be obtained through improving antibiotic use and optimizing the hygiene practices, [14][15][16] the impact of ASP interventions aimed at reducing inappropriate NAAT is beginning to emerge. Kociolek 21 utilized a similar clinical decision support tool and demonstrated decreased inappropriate testing and avoidance of testing among patients with concomitant laxative use.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major risk factors for H. pylori infection is the long-term use of proton pump inhibitors (PPI), which are also regarded as a notable risk factor for CDI. Taking this into account, Lewis et al conducted a retrospective cohort study that targeted proton pump inhibitor use and probiotics and concluded that decreasing PPI use and increasing probiotic use decreases the risk of hospital-acquired CDI [19].…”
Section: Reviewmentioning
confidence: 99%